Acquisition of E5 Galileo Signals in Matlab. (2015) - Stepanova, Ekaterina; Kudryavtsev, Ilya; Lohan, Elena Simona
Abstract: The deployment of Galileo constellation leads to the need of efficient algorithms for acquisition and tracking of Galileo signals. These signals are different from GPS signals and this difference should be taken into consideration in the program code. This paper deals with the acquisition of Galileo signals in Matlab. The code is developed on the basis of the free code developed by Kai Borre for GPS Software defined radio[1] .